Pathophysiological, clinical and treatment repercussions of Wernicke's Encephalopathy: a review - Fonseca, Gustavo Soares Gomes Barros (2021)
Among the encephalopathies, some have been more studied in recent decades, such as Wernicke's encephalopathy (WE), which is a set of neuropsychiatric signs and symptoms that result from a nutritional deficiency of thiamine. This research is a systematic bibliographic review, of the quantitative type, which used the platforms PubMed, Scientific Electronic Library Online (SciELO) and Google Scholar as a database for researching scientific articles. Literature published with a time frame from 2016 to 2021, in English, that addressed Wernicke's Encephalopathy and its pathophysiological and clinical aspects were used. Therefore, it was found that the deficiency of thiamine (vitamin B1) is able to lead the patient to develop Wernicke's encephalopathy, when the disease is associated with anterograde amnesia. Furthermore, the underlying condition described in WE is alcoholism. Therefore, high doses of parenteral thiamine in high-risk patients are essential for the patient's gradual improvement.